(x + y)^2 = (x^2 - 2xy + y^2)
First distribute the ^2 on the left side of the equation to each term inside the parenthesis:
x^2+ 2xy + y^2
Now pick one of the variables to solve for and isolate it:
(solving for x)
x^2 + 2xy + y^2 = x^2 - 2xy + y^2
x^2+ 2xy = x^2 - 2xy
2xy = -2xy
-x = x
x = 0
When you solve for y in the equation it will turn out to be 0 as well
Velocity=Distance/Time
Time(t)=Distance/Velocity
☺☺☺☺
Answer:
7.irrational
8.integer ,whole number ,rational number
Step-by-step explanation:
7. that dash line on top of decimal shows that its keeps repeating
8. -18/6 = -3
The equation:
y - y 1 = ( y2 - y1 ) / ( x2- x1) * ( x - x1 )
y - ( - 5 ) = ( 4 + 5 ) / ( - 5 + 7 ) * ( x - ( - 7 ) )
y + 5 = 9/2 ( x + 7 )
y + 5 = 9/2 x + 63 /2 / * 2
2 y + 10 = 9 x + 63
- 9 x + 2 x = 53
Answer:
C ) y + 5 = 9/2 ( x + 7 ) ; - 9 x + 2 y = 53